Design and Build an Expert System in the Diagnosis of Ear, Nose and Throat Diseases by Using the Certainty Factor Method - Indra Kurniawan (Institute of Computer Science (IOCS), 2020)
Symptoms of ENT disease (Ear, Nose and Throat) are often underestimated by some people. Even though these symptoms may refer to a serious ENT disease. Therefore, this final project aims to implement an expert system with the Certainty Factor (CF) method in cases of early diagnosis of ENT disease. The ENT diseases in question are otitis externa, otitis media, pharyngitis, tonsillitis, sinusitis and allergic rhinitis. odor, headache / swallowing, decreased hearing function, coughing, fever, sore throat and snoring sleep. Furthermore, for each of these symptoms, an expert CF value was searched. After that, rules are formed according to the symptoms of ENT diseases that refer to certain ENT diseases. Then the user test will produce the user's CF value, so that the final CF value will be used as a value in making decisions from sequential CF calculations between user CF and expert CF and knowing the level of diagnosed disease, namely the level of symptoms or the acute level.